Recognition of Customary Norms Within the Framework of Indonesian Legal Positivism - Firdaus Arifin; I Gde Pantja Astawa; Ihsanul Maarif; Dewi Sulastri; Mohd Kamarulnizam Abdullah (Khazanah Hukum, 2025)
The recognition of customary norms within Indonesia’s legal system continues to face challenges due to the dominance of legal positivism, which emphasizes legal certainty through codified regulations. Although Article 18B (2) of the 1945 Constitution acknowledges the existence of indigenous legal communities, its implementation within the national legal system remains limited and conditional, leading to legal uncertainty for indigenous groups. This study aims to analyze how customary norms are recognized within Indonesia’s positive legal system and to identify the challenges and opportunities in harmonizing these two legal frameworks. This research employs a normative legal method with a conceptual and statutory approach, analyzed qualitatively using a descriptive-analytical framework. The findings reveal that customary law remains marginalized within the national legal system due to inconsistencies in regulations and court rulings, as well as the absence of a clear harmonization mechanism. The implications of this study emphasize the need for more inclusive legal reforms, enhanced capacity-building for law enforcement officials, and a stronger role for Indigenous communities in legal policymaking. These measures are expected to strengthen the recognition of customary law within the national legal system, contributing to greater substantive justice for Indigenous communities.